2007
DOI: 10.3201/eid1310.070252
|View full text |Cite
|
Sign up to set email alerts
|

Foot-and-Mouth Disease Virus Serotype A in Egypt

Abstract: We describe the characterization of a foot-and-mouth disease (FMD) serotype A virus responsible for recent outbreaks of disease in Egypt. Phylogenetic analysis of VP1 nucleotide sequences demonstrated a close relationship to recent FMD virus isolates from East Africa, rather than to viruses currently circulating in the Middle East.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
68
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 10 publications
(10 reference statements)
1
68
0
Order By: Relevance
“…If the latter, this situation may not be particular to SAT 2: a new serotype A virus with a probable origin in sub-Saharan Africa was also discovered in Egypt in 2012 (), although whether this was a genuinely new introduction in the very recent past seems an open question, given the fairly frequent occurrence of serotype A in the country (27, 28). …”
Section: Discussionmentioning
confidence: 99%
“…If the latter, this situation may not be particular to SAT 2: a new serotype A virus with a probable origin in sub-Saharan Africa was also discovered in Egypt in 2012 (), although whether this was a genuinely new introduction in the very recent past seems an open question, given the fairly frequent occurrence of serotype A in the country (27, 28). …”
Section: Discussionmentioning
confidence: 99%
“…There is always a fear of introducing FMDV into a FMDV-free country or a new serotype into a FMDV-endemic country. For example serotype O was endemic in Egypt since 1960 [5], and in 2006, type A was introduced and caused a FMD outbreak [6]. Recently, SAT 2 was the primary cause of a FMD epidemic in Egypt which erupted in February 2012 and led to 82362 suspected cases, of which 19655 died [7].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it has been demonstrated that certain serotype A viruses, which have circulated in the Horn of Africa, have been able to spread as far as Egypt in North Africa and Kenya in East Africa through animal trade (Knowles et al, 2007). The VP1 protein also contains important antigenic sites and an arg-gly-asp (RGD) motif that binds to certain integrin receptors on the host cell surface and is part of a larger sequence (RGDLXXL) that is conserved for effective interaction of the virus with the host cell (Sobrino et al, 2001;Jackson et al, 2003).…”
Section: Introductionmentioning
confidence: 99%